The way, the truth and the life series - Cooney, Marcellina; Edwards, Angela; Ley, Amette (Teachers' Enterprise in Religious Education Co. Ltd, 2011)
Contents: Introduction -- 1. God's great plan -- 2. Mary our mother -- 3. Families and celebrations -- 4. Following Jesus -- 5. The resurrection -- 6. Miracles